Comparison of a six degree-of-freedom force sensor and pressure insole measurements in selected skiing manoeuvres - Kersting, U. G.; Kurpiers, N.; Hild, E.; Kiefmann, A.; Senner, V. (ESM 2010 emed scientific meeting, 2010)
Alpine skiing has been characterized as particularly dangerous to the knee joint (Heir et al., 2005). Many of these may be avoidable with a greater understanding of biomechanical parameters related to skiing technique and equipment design. Attempts to measure the dynamic forces transferred to the skier have been described previously. Only few have successfully realized a full six degree-of-freedom measurement system due to the high technical challenges implied (Kiefmann et al., 2006). Alternatively, pressure insole systems have been used to collect data during skiing with different applications and studies (Schaff et al., 1989). The purpose of this investigation was to compare a pressure insole in combination with a pressure sensor placed inside the shaft at the anterior aspect of the tibia to the data collected from a full six degree-of-freedom force sensor mounted between shoe and binding. It was hypothesized that vertical reaction forces and the moment about the ankle joint can be estimated from pressure measurements.